ST2 expression and release by the bronchial epithelium is downregulated in asthma. Issue 12 (27th July 2020) - Kaur, Davinder; Chachi, Latifa; Gomez, Edith; Sylvius, Nicolas; Singh, Shailendra R.; Ramsheh, Mohammadali Y.; Saunders, Ruth; Brightling, Christopher E.
Abstract: Background: The airway epithelium plays an important role in wound repair, host defense and is involved in the immunopathogenesis of asthma. Genome wide association studies have described associations between ST2/Interleukin (IL)‐33 genes in asthma, but its role in bronchial epithelium is unclear. Methods: ST2 expression was examined in subjects with asthma and healthy controls in bronchial epithelium from biopsies (n = 27 versus n = 9) and brushings (n = 34 versus n = 20) by immunohistochemistry and RNA‐Seq. In human primary bronchial epithelial cells ST2 mRNA and protein expression were assessed by qPCR, flow cytometry, Western blotting, and immunofluorescence. IL‐33 function in epithelial cells was examined by intracellular calcium measurements, wound healing assays, and synthetic activation by gene array and ELISA. Results: Bronchial epithelial ST2 protein expression was significantly decreased in biopsies in subjects with asthma compared to healthy controls ( P  = .039). IL1RL1 gene expression in bronchial brushes was not different between health and disease. In vitro primary bronchial epithelial cells expressed ST2 and IL‐33 stimulation led to an increase in intracellular calcium, altered gene expression, but had no effect upon wound repair. Epithelial cells released sST2 spontaneously, which was reduced following stimulation with TNFα or poly‐IC. Stimulation by TNFα or poly‐IC did not affect the total ST2 expression by epithelial cell whereas surface ST2 decreased in response to TNFα, but not poly‐IC. Conclusion: In asthma, bronchial epithelium protein expression of ST2 is decreased. Our in vitro findings suggest that this decrease might be a consequence of the pro‐inflammatory environment in asthma or in response to viral infection. Abstract : ST2 and soluble ST2 was expressed by primary and BEAS‐2B epithelial cells in vitro and ST2 expression was significantly lower in bronchial epithelium in subjects with asthma compared to healthy controls. TNF‐α and poly‐IC treatment of primary bronchial epithelial cells resulted in down regulation of soluble ST2 whereas only TNF‐α contributed to the reduction of ST2 receptor. Downregulation of the release of soluble ST2 could potentially increase free IL‐33 leading to amplification of the underlying airway inflammation in asthma. Abbreviations: IL‐1RAcP, interleukin‐1 receptor accessory protein; poly‐IC, polyinosinic‐polycytidylic acid; ST2L, transmembrane bound isoform; sST2, soluble ST2